Proses Perencanaan Media di Advertising Agency PT. Citra Surya Indonesia pada Brand Wardah - Iga Desara; Velda Ardia (Journal on Education, 2023)
Media planning is the process of developing a scheduling plan that shows how advertising time and space will achieve marketing objectives. PT. Citra Surya Indonesia designed an effective media planning process to provide information about Wardah products offered to potential customers so as to attract consumer interest and to increase awareness by a larger number by using conventional media as a tool to reach all regions, PT. Citra Surya Indonesia uses television, radio and ooh media. The purpose of this study was to determine the media planning process used by PT. Citra Surya Indonesia and what obstacles were encountered in the media planning process at PT. Indonesian Solar Image. The theory in this study uses theory from the literature review, namely the planning process, agency, advertising agency, wardah. This study uses descriptive qualitative. The agency object in this study is PT. Indonesian Solar Image. By using data collection interviews with resource persons Media Planner PT. Citra Surya Indonesia and triangulation of sources and documentation. From the results of this study it was concluded that the media planning process is divided into several stages forming Marketing Strategy, Advertising Objectives, Advertising Budget, Message Strategy, Media Planning and Media Planning consisting of Selection of Target Audiences, Specification of Objectives, Selection of Media and Facilities, Media Purchases.